Microplastics in Marine and Estuarine Species From the Coast of Portugal - Pequeno, João; Antunes, Joana; Dhimmer, Viren; Bessa, Filipa; Sobral, Paula (Frontiers in Environmental Science, 2021)
Microplastics (MP) have been confirmed as emerging pollutants in the marine environment due to their ubiquity, bioavailability, persistence and potential toxicity. This study contributes with valuable data regarding the abundance and characteristics of the MP found in five species collected from Portugal. The mussel Mytilus galloprovincialis (n = 140) was collected from the Tagus estuary and Porto Covo coastal area, the peppery furrow shell Scrobicularia plana (n = 140) and the polychaete Marphysa sanguinea (n = 30) both from the Sado estuary, and Trachurus trachurus (n = 82) and Scomber colias (n = 82) fished off Figueira da Foz and Sesimbra. Soft tissues of all individuals were digested using a KOH (10%) solution, which allowed the extraction of MP. All studied species presented MP. In a total of 502 MP observed from all samples, 80% were fibers and 20% were fragments, with a size range of 73 μm–4,680 μm and blue was the most common color recorded (46%). The frequency of occurrence of MP was higher in T. trachurus (70%) and lowest in M. sanguinea (17%). MP abundance ranged from 0.30 ± 0.63 MP. ind−1 in S. plana, to 2.46 ± 4.12 MP. ind−1 in S. colias. No significant correlation was found between the individual biometric parameters and total MP, fibers and fragments ingested by each species. The FTIR analysis revealed that polyester and polyethylene were the most common polymers present. These results can be used as a reference for future studies regarding the use of indicator species for monitoring MP pollution in the coast of Portugal.